Party down - Scott, Adam 1973-; Marino, Ken 1968-; Lynch, Jane 1960-; Hansen, Ryan 1981-; Starr, Martin 1982-; Caplan, Lizzy 1982- (Anchor Bay Entertainment, 2010)
A group of struggling dreamers are stuck working for tips while waiting for their big break. As employees of the L.A. catering company 'Party Down, ' these misfits mingle with guests at everything from sweet sixteen parties to the most lavish Hollywood soirees. Follow these engaging wannabes as they wait on guests while waiting on something better to come along
TV-Serie. USA. 2021-
Keywords: Television series; Comedy films; Fernsehserie; Filmkomödie; Caterers and catering / Drama; Parties / Drama; Caterers and catering; Parties; DVD-Video discs; Television comedies; Television programs; Drama; Fiction television programs; Television programs for the hearing impaired; Comedy television programs; Comédies télévisées; Émissions télévisées pour personnes handicapées auditives; DVD-Video